Study guides

☆☆

Q: What is 6z plus 4-4z equals 6 plus z-7 simplified?

Write your answer...

Submit

Still have questions?

Related questions

6z + 28 = 12z + 10 18 = 6z 3 = z

15z+5+6z=0 21z+5=0 z=-5/21

6z+28=12z+10 6z-12z=10-28 addition property of equality. -6z=-18 simplification z=3 multiplication property of equality.

Is an equation of a straight line in 3 dimensions. It cannot be simplified further, and a solution for any of the variables requires another two [independent] equations.

1 plus 6 zeroes equals 1 million (1,000,000).

2z+6z+24=0 8z+24=0 8z= -24 z= - 3

-6z + 16 = 52 subtract 16 from each side -6z = 36 divide by -6 z = -6

63 + 20 - 60 = 23

-6z + 2 = 3z + 4z + 28 Add 6z to both sides: 2 = 3z + 4z + 28 + 6z = 28 + 13z Subtract 28 from both sides: - 26 = 13z Divide both sides by 13: -2 = z

-5x+7y-6z

z equals 7

-6z 2 = 3z+ 4z+28 -6z+2 +3z = 3z+ 4z +28 +4z -6z+4z+2 = 3z+ 28 -10z+2 -3z= 28 - 2 -10z + -3z = 26 -13z/13 = 26/-13 z = -2

3x 3y + 6z = 12

6z - 8 - 2 + 3 = 0 combining all the constant terms: 6z -7 = 0 adding 7 to both sides: 6z = 7 dividing both sides by 6: z = 7/6

z = 18.5 6z - 24 = 2z + 50 Take the -24 to the other side of the equals and change its sign; take the 2z to the other side of the equals and change its sign: => 6z - 2z = 50 + 24 => 4z = 74 Divide both sides by 4: => z = 18.5

If 6z=17, divide both sides by 6 z=17/6

-47 + 6z = 3z-2-3z -3z-47 + 3z = -2+47 +473z = 45/3 /3z = 15

You can't simplify it any further than 3x+2y+6z=24, unless you have been given values of x,y and z or other equations to find x,y and z.

Since there are no given triplets, none of them!

17z + 34 = 6z + 5 17z - 6z + 34 = 6z - 6z + 5 11z + 34 = 5 11z + 34 - 34 = 5 - 34 11z = -29 11z/11 = -29/11 z = -2 7/11 or -29/11 Double check your answer: 17z + 34 = 6z + 5 17(-2 7/11) + 34 = 6z + 5 -44 9/11 + 34 = 6z + 5 -10 9/11 = 6z + 5 -10 9/11 = 6(-2 7/11) + 5 -10 9/11 = -15 9/11 + 5 -10 9/11 = -10 9/11 17z + 34 = 6z + 5 when Z = -2 7/11

14

The result will be a plane that intercepts the x-, y-, and z-axes at +9, +6, and +3, respectively.

6z - 3 = 0

The list of choices that accompanies the question is really short.2x + 3y + 6z = 54At the y-intercept, 'x' and 'z' are zero.3y = 54y = 18

6z =

People also asked